2012
DOI: 10.1245/s10434-012-2779-3
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma: 30-Year Experience from a Single Institution

Abstract: SLNB identifies micrometastasis in one-third of early-stage patients. Negative SLNB may predict for improved but not necessarily favorable outcome. Initial tumor size and clinical nodal disease predict for poor outcome. High recurrence rates warrant the development of more effective adjuvant therapies, and better markers of recurrence and treatment response for MCC are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 55 publications
5
109
0
1
Order By: Relevance
“…Although virtually all patients are initially rendered free of detectable disease, roughly half of these patients will recur [95,96]. Once distant metastatic disease arises, cytotoxic chemotherapy leads to a response in >50% of cases, but the median time to progression is only 3 months and durable responses are exceedingly rare [97].…”
Section: Treatment Of MCCmentioning
confidence: 99%
“…Although virtually all patients are initially rendered free of detectable disease, roughly half of these patients will recur [95,96]. Once distant metastatic disease arises, cytotoxic chemotherapy leads to a response in >50% of cases, but the median time to progression is only 3 months and durable responses are exceedingly rare [97].…”
Section: Treatment Of MCCmentioning
confidence: 99%
“…These tumors grow rapidly and tend to metastasize early and frequently to local regions of the body, leading to a relatively poor prognosis with this aggressive disease [2,3,5]. Among patients diagnosed with local or regional disease, the reported rates of recurrence range from 43 to 48% [6,7]. The 5-year overall survival (OS) rate is 40% [1] and the mortality rate with MCC is greater than that with other skin cancers, including melanoma [4].…”
mentioning
confidence: 99%
“…However, the data on the prognostic implication of SLNB in MCC are mixed, and it is unclear if it carries the same prognostic guidance as it does for melanoma [64]. A report from Memorial Sloan Kettering found that SLN-positive patients received more adjuvant therapy, however, their 2-year recurrence and survival rates were not significantly different (12 vs 12%; p = 0.86 and 6.1 vs 5.7%; p = 0.89) [65].…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%